Analisis Kemampuan Literasi Kimia Mahasiswa melalui Pemberian Soal Berbasis Kontekstual - Ruslan, Zuhrah Adminira; Agus, Jasdar (Chemistry Education Review (CER), 2024)
This research aims to analyze the chemical literacy abilities of students in the Department of Chemistry, Education Class B, UNM Class of 2022, by providing contextual-based exam questions and student response questionnaires using quantitative descriptive analysis methods. The results of the study showed that 84% of the student sample had chemical literacy skills in the medium category, with a score of 42.07 when given contextual-based exam questions. The results of scientific competence as measured in scientific literacy can be improved by routinely providing students with reading material about chemical literacy that is related to scientific phenomena and is appropriate to the context of everyday life. Knowledge of the chemistry learning context and interpreting accurate data emphasizes the use of scientific principles to solve problems according to their application in everyday life, based on student competence in using scientific evidence. There is great enthusiasm for implementing contextual learning, as seen in the questionnaire results of responses given by students through contextual-based questions, which can help students pay attention to what they are learning.